Sulfur Biogeochemistry of an Oil Sands Composite Tailings Deposit - Warren, Lesley A.; Kendra, Kathryn E.; Brady, Allyson L.; Slater, Greg F. (Frontiers in Microbiology, 2016)
Composite tailings (CT), an engineered, alkaline, saline mixture of oil sands tailings (FFT), processed sand and gypsum (CaSO4; 1 kg CaSO4 per m3 FFT) are used as a dry reclamation strategy in the Alberta Oil Sands Region (AOSR). It is estimated that 9.6 × 108 m3 of CT are either in, or awaiting emplacement in surface pits within the AOSR, highlighting their potential global importance in sulfur cycling. Here, in the first CT sulfur biogeochemistry investigation, integrated geochemical, pyrosequencing and lipid analyses identified high aqueous concentrations of ∑H2S (>300 μM) and highly altered sulfur compounds composition; low cell biomass (3.3 × 106– 6.0 × 106 cells g−1) and modest bacterial diversity (H' range between 1.4 and 1.9) across 5 depths spanning 34 m of an in situ CT deposit. Pyrosequence results identified a total of 29,719 bacterial 16S rRNA gene sequences, representing 131 OTUs spanning19 phyla including 7 candidate divisions, not reported in oil sands tailings pond studies to date. Legacy FFT common phyla, notably, gamma and beta Proteobacteria, Firmicutes, Actinobacteria, and Chloroflexi were represented. However, overall CT microbial diversity and PLFA values were low relative to other contexts. The identified known sulfate/sulfur reducing bacteria constituted at most 2% of the abundance; however, over 90% of the 131 OTUs identified are capable of sulfur metabolism. While PCR biases caution against overinterpretation of pyrosequence surveys, bacterial sequence results identified here, align with phospholipid fatty acid (PLFA) and geochemical results. The highest bacterial diversities were associated with the depth of highest porewater [∑H2S] (22–24 m) and joint porewater co-occurrence of Fe2+ and ∑H2S (6–8 m). Three distinct bacterial community structure depths corresponded to CT porewater regions of (1) shallow evident Fe(II) (<6 m), (2) co-occurring Fe(II) and ∑H2S (6–8 m) and (3) extensive ∑H2S (6–34 m) (UniFrac). Candidate divisions GNO2, NKB19 and Spam were present only at 6–8 m associated with co-occurring [Fe(II)] and [∑H2S]. Collectively, results indicate that CT materials are differentiated from other sulfur rich environments by modestly diverse, low abundance, but highly sulfur active and more enigmatic communities (7 candidate divisions present within the 19 phyla identified).